Thermosolutal instability of Walters' rotating fluid (Model B') in porous medium - Sharma, R.C.; Sunil, -; Chand, Suresh (Archives of Mechanics, 1999)
The thermosolutal instability of Walters' (Model B') fluid in porous medium is considered in the presence of uniform vertical rotation. For the case of stationary convection, the stable solute gradient and rotation have stabilizing effects on the system, whereas the medium permeability has a destabilizing (or stabilizing) effect on the system under certain conditions. The dispersion relation is also analysed numerically. It has also been shown that as rotation parameter increases, the stabilizing range of medium also increases. The kinematic viscoelasticity has no effect on the stationary convection. The stable solute gradient, rotation, porosity and kinematic viscoelasticity introduce oscillatory modes in the system, which did not occur in their absence. The sufficient conditions for the non-existance of overstability are also obtained.